Sustainable E-Waste Management in the Age of Smart Devices: A Study Based on the KAP Model - Hamim, Siti Juliana; Ahmad, Nur Farahiyah Sidik; Hashim, Nurul Nadiah (Tropical Scientific Journal, 2026)
Objective: The study aims to assess the level of knowledge, attitudes, and practices (KAP) related to e-waste management among students of Kolej Komuniti Bentong (KKBEN) in the context of increasing smart device usage. It also examines the relationships among these three factors to better understand the determinants of sustainable e-waste management behavior. Research Method: A quantitative survey design was employed involving 120 students selected through simple random sampling. Data were collected using a structured questionnaire covering demographic information and students’ knowledge, attitudes, and practices regarding e-waste management. Descriptive and inferential analyses, including correlation tests, were conducted using SPSS Version 27. Findings: Students demonstrated moderately high levels of knowledge (M = 3.56, SD = 0.93), attitude (M = 3.55, SD = 0.95), and practice (M = 3.40, SD = 1.02) toward e-waste management. Correlation results revealed significant positive relationships between knowledge and attitude (r = 0.678, ρ < .001), knowledge and practice (r = 0.487, ρ < .001), and attitude and practice (r = 0.539, ρ < .001). These findings indicate that higher knowledge and more positive attitudes are associated with better e-waste management practices. Originality: This study provides empirical validation of the KAP model within the context of e-waste management among Malaysian community college students. It highlights the critical role of environmental education, awareness initiatives, and institutional support in shaping sustainable behaviors, particularly within technical and vocational education settings